Facile synthesis and characterization of ZnO nanoparticles grown on halloysite nanotubes for enhanced photocatalytic properties - Hongxia Peng (Nature Portfolio, 2017)
Abstract We demonstrated herein that ZnO nanoparticle with sizes in the range of 3–5 nm grown on the surface of halloysite nanotubes (HNTs) could be facile prepared in large quantities through the seed-mediated growth process using ZnAc2·2H2O as the zinc source. Compared with the individually dispersed ZnO nanoparticles, the as-prepared HNTs@ZnO nanocomposites showed a smaller band gap energy and relatively strong light absorption. Therefore, HNTs@ZnO nanocomposites possessed higher photocatalytic activity than individually dispersed ZnO nanoparticles, exhibiting the HNTs@ZnO nanocomposites could be used as highly efficient photocatalysts. The HNTs@ZnO nanocomposites endowed HNTs special performance and improve the catalytic activity of ZnO, which originated from narrow band gap and chemical passivation induced by a negative fixed charge in the HNTs support.